SKIN-COVERED MASKS FROM THE CROSS RIVER REGION OF NIGERIA AND CAMEROON AT THE NATIONAL MUSEUM OF AFRICAN ART: A TECHNICAL STUDY. Issue 3 (August 2014) - Owczarek, Nina
Abstract : Nineteen skin-covered masks from the Cross River region of Nigeria and Cameroon were studied at the National Museum of African Art. The construction of the masks are documented and compared against existing field literature. Results of analyses of the wood, skin, and surface applications are included, as well as detail images of construction features. In addition to visual examination, x-radiography, thin section, deoxyribonucleic acid, portable x-ray fluorescence, x-ray diffraction, and Fourier transform infrared analysis techniques were employed in the examination. For the most part, this study showed the skin-covered masks in the NMAfA collection support the basics of the field literature descriptions while also illustrating a wider variety in techniques and materials.